Enhancing prioritization strategies of natural extracts: integrating heterogeneous data from metabolomics datasets and biological screenings into knowledge graphs - Luis-Manuel Quiros-Guerrero; Frederic Burdet; Olivier Kirchhoffer; Paola Haemmerli; Louis-Felix Nothias; Pierre-Marie Allard; Arnaud Gaudry; Jahn Nitschke; Nabil Hanna; Sébastien Moretti; Robin Engler; Florence Mehl; et al. (Phytochemistry Letters, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

Dome permeability and fluid circulation at La Soufrière de Guadeloupe implied from soil CO$$_2$$ degassing, thermal flux and self-potential - Amelie Klein; David E. Jessop; Franck Donnadieu; Joanny Pierre; Roberto Moretti (Bulletin of Volcanology, 2024)

Quantifying the response of Blainville's beaked whales to U.S. naval sonar exercises in Hawaii - Eiren K. Jacobson; E. Elizabeth Henderson; David L. Miller; Cornelia S. Oedekoven; David J. Moretti; Len Thomas (Marine Mammal Science, 2022)
Behavioral responses of beaked whales (family Ziphiidae) to naval use of mid‐frequency active sonar (MFAS) have been quantified for some species and regions. We describe the effects of MFAS on the probability of detecting diving groups of Blainville's beaked whales on the U.S. Navy Pacific Missile Range Facility (PMRF) in Hawaii and compare our results to previously published results for the same species at the Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. We use passive acoustic data collected at bottom‐mounted hydrophones before and during six naval training exercises at PMRF along with modelled sonar received levels to describe the effect of training and MFAS on foraging groups of Blainville's beaked whales. We use a multistage generalized additive modeling approach to control for the underlying spatial distribution of vocalizations under baseline conditions. At an MFAS received level of 150 dB re 1 μPa rms the probability of detecting groups of Blainville's beaked whales decreases by 77%, 95% CI [67%, 84%] compared to periods when general training activity was ongoing and by 87%, 95% CI [81%, 91%] compared to baseline conditions. Our results indicate a more pronounced response to naval training and MFAS than has been previously reported.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Spatial Analysis of Beaked Whale Foraging During Two 12 kHz Multibeam Echosounder Surveys - Hilary Kates Varghese; Kim Lowell; Jennifer Miksis-Olds; Nancy DiMarzio; David Moretti; Larry Mayer (Frontiers in Marine Science, 2021)
To add to the growing information about the effect of multibeam echosounder (MBES) operation on marine mammals, a study was conducted to assess the spatial foraging effort of Cuvier’s beaked whales during two MBES surveys conducted in January of 2017 and 2019 off of San Clemente Island, California. The MBES surveys took place on the Southern California Antisubmarine Warfare Range (SOAR), which contains an array of 89 hydrophones covering an area of approximately 1800 km 2 over which foraging beaked whales were detected. A spatial autocorrelation analysis of foraging effort was conducted using the Moran’s I (global) and the Getis-Ord Gi ∗ (local) statistics, to understand the animals’ spatial use of the entire SOAR, as well as smaller areas, respectively, within the SOAR Before, During , and After the two MBES surveys. In both years, the global Moran’s I statistic suggested significant spatial clustering of foraging events on the SOAR during all analysis periods ( Before, During , and After ). In addition, a Kruskal-Wallis (comparison) test of both years revealed that the number of foraging events across analysis periods were similar within a given year. In 2017, the local Getis-Ord Gi ∗ analysis identified hot spots of foraging activity in the same general area of the SOAR during all analysis periods. This local result, in combination with the global and comparison results of 2017, suggest there was no obvious period-related change detected in foraging effort associated with the 2017 MBES survey at the resolution measurable with the hydrophone array. In 2019, the foraging hot spot area shifted from the southernmost corner of the SOAR Before , to the center During , and was split between the two locations After the MBES survey. Due to the pattern of period-related spatial change identified in 2019, and the lack of change detected in 2017, it was unclear whether the change detected in 2019 was a result of MBES activity or some other environmental factor. Nonetheless, the results strongly suggest that the level of detected foraging during either MBES survey did not change, and most of the foraging effort remained in the historically well-utilized foraging locations of Cuvier’s beaked whales on the SOAR.

Abundance, survival, and annual rate of change of Cuvier's beaked whales ( Ziphius cavirostris ) on a Navy sonar range - K. Alexandra Curtis; Erin A. Falcone; Gregory S. Schorr; Jeffrey E. Moore; David J. Moretti; Jay Barlow; Erin Keene (Marine Mammal Science, 2021)
Bayesian mark‐recapture estimates of survival, abundance, and trend are reported for Cuvier's beaked whales ( Ziphius cavirostris ) using a Navy training range off southern California. The deep‐diving beaked whale family is exceptionally vulnerable to mid‐frequency active sonar (MFAS), which has been implicated in mass strandings and altered foraging behavior. Extremely low sighting probabilities impede studies of population‐level impacts of MFAS on beaked whales. The San Nicolas Basin hosts a Navy training range subject to frequent MFAS use and attracts high densities of Z. cavirostris . An 11‐year (2007–2018) photo‐identification program leveraged automated acoustic detection and location capabilities on the range's 1,800‐km 2 hydrophone array to enhance capture probability. Estimated population parameters for Z. cavirostris using the range included mean (90% credibility intervals) apparent annual survival of 0.950 (0.899–0.986), annual number of individuals as 121 (71–219), and annual rate of change of −0.8% (−5.6%–4.1%). Simulations show the probability of detecting abundance changes is currently low, but can be greatly improved through continued monitoring and increased effort. Complementary data collection on habitat use and demographic rates in San Nicolas and surrounding basins is also essential to relating direct effects of MFAS use to changes in vital rates and broader population outcomes.

A multi-decadal view of the heat and mass budget of a volcano in unrest: La Soufrière de Guadeloupe (French West Indies) - David E. Jessop; Séverine Moune; Roberto Moretti; Dominique Gibert; Jean-Christophe Komorowski; Vincent Robert; Michael J. Heap; Alexis Bosson; Magali Bonifacie; Sébastien Deroussi; Céline Dessert; Marina Rosas-Carbajal; et al. (Bulletin of Volcanology, 2021)

The origin of urban communities: From the regional species pool to community assemblages in city - Bertrand Fournier; David Frey; Marco Moretti (Journal of Biogeography, 2020)
Aim Cities worldwide are characterized by unique human stressors that filter species based on their traits, potentially leading to biodiversity loss. The knowledge of which species are filtered and at which scale is important to gain a more mechanistic understanding of urban community assembly and to develop strategies to manage human impact on urban ecosystems. We investigate the ecological mechanisms shaping urban community assembly, taking into account changes across scales, taxa and urban green space types. Location City of Zurich, Switzerland. Taxon Carabid beetles and wild bees. Methods We use a large species occurrence and trait dataset with a high spatial resolution to assess the filtering effect of a medium‐sized city on a regional pool of potential colonists. We then assess the filtering from the urban pool to five widely distributed types of urban green spaces. Results We found that our model city selects for functionally similar but taxonomically diverse bee and carabid beetle species from the regional species pool. Within the city, community assembly processes vary among green space types and taxa resulting in important changes in community taxonomic and functional composition. Main conclusions Our findings suggest that urban community assembly is a multi‐scale process dominated by the strong environmental filtering from a regional to an urban species pool. This leads to the selection of species pre‐adapted to urban conditions. Spatial habitat heterogeneity within and among UGS types can maintain an important taxonomic diversity within cities. However, increasing urban functional diversity would require stronger management efforts that consider regional ecological processes.

Behavioral responses of satellite tracked Blainville's beaked whales ( Mesoplodon densirostris ) to mid‐frequency active sonar - Trevor W. Joyce; John W. Durban; Diane E. Claridge; Charlotte A. Dunn; Leigh S. Hickmott; Holly Fearnbach; Karin Dolan; David Moretti (Marine Mammal Science, 2020)
The vulnerability of beaked whales (Family: Ziphiidae) to intense sound exposure has led to interest in their behavioral responses to mid‐frequency active sonar (MFAS, 3–8 kHz). Here we present satellite‐transmitting tag movement and dive behavior records from Blainville's beaked whales ( Mesoplodon densirostris ) tagged in advance of naval sonar exercises at the Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. This represents one of the largest samples of beaked whales individually tracked during sonar operations ( n = 7). The majority of individuals (five of seven) were displaced 28–68 km after the onset of sonar exposure and returned to the AUTEC range 2–4 days after exercises ended. Modeled sound pressure received levels were available during the tracking of four individuals and three of those individuals showed declines from initial maxima of 145–172 dB re 1 μPa to maxima of 70–150 dB re 1 μPa following displacements. Dive behavior data from tags showed a continuation of deep diving activity consistent with foraging during MFAS exposure periods, but also suggested reductions in time spent on deep dives during initial exposure periods. These data provide new insights into behavioral responses to MFAS and have important implications for modeling the population consequences of disturbance.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of garden management practices, by different types of gardeners, on human wellbeing and ecological and soil sustainability in Swiss cities - Robert Home; Olivia Lewis; Nicole Bauer; Andreas Fliessbach; David Frey; Stéphanie Lichtsteiner; Marco Moretti; Simon Tresch; Christopher Young; Andrea Zanetta; Matthias Stolze (Urban Ecosystems, 2019)

Biotic interactions in species distribution modelling: 10 questions to guide interpretation and avoid false conclusions - Carsten F. Dormann; Maria Bobrowski; D. Matthias Dehling; David J. Harris; Florian Hartig; Heike Lischke; Marco D. Moretti; Jörn Pagel; Stefan Pinkert; Matthias Schleuning; Susanne I. Schmidt; Christine S. Sheppard; et al. (Global Ecology and Biogeography, 2018)
Aim Recent studies increasingly use statistical methods to infer biotic interactions from co‐occurrence information at a large spatial scale. However, disentangling biotic interactions from other factors that can affect co‐occurrence patterns at the macroscale is a major challenge. Approach We present a set of questions that analysts and reviewers should ask to avoid erroneously attributing species association patterns to biotic interactions. Our questions relate to the appropriateness of data and models, the causality behind a correlative signal, and the problems associated with static data from dynamic systems. We summarize caveats reported by macroecological studies of biotic interactions and examine whether conclusions on the presence of biotic interactions are supported by the modelling approaches used. Findings Irrespective of the method used, studies that set out to test for biotic interactions find statistical associations in species’ co‐occurrences. Yet, when compared with our list of questions, few purported interpretations of such associations as biotic interactions hold up to scrutiny. This does not dismiss the presence or importance of biotic interactions, but it highlights the risk of too lenient interpretation of the data. Combining model results with information from experiments and functional traits that are relevant for the biotic interaction of interest might strengthen conclusions. Main conclusions Moving from species‐ to community‐level models, including biotic interactions among species, is of great importance for process‐based understanding and forecasting ecological responses. We hope that our questions will help to improve these models and facilitate the interpretation of their results. In essence, we conclude that ecologists have to recognize that a species association pattern in joint species distribution models will be driven not only by real biotic interactions, but also by shared habitat preferences, common migration history, phylogenetic history and shared response to missing environmental drivers, which specifically need to be discussed and, if possible, integrated into models.

Insights into Blainville's beaked whale ( Mesoplodon densirostris ) echolocation ontogeny from recordings of mother‐calf pairs - Charlotte Dunn; Diane Claridge; John Durban; Jessica Shaffer; David Moretti; Peter Tyack; Luke Rendell (Marine Mammal Science, 2017)

Monitoring population‐level responses of marine mammals to human activities - Erica Fleishman; Daniel P. Costa; John Harwood; Scott Kraus; David Moretti; Leslie F. New; Robert S. Schick; Lisa K. Schwarz; Samantha E. Simmons; Len Thomas; Randall S. Wells (Marine Mammal Science, 2016)
We provide guidance for monitoring whether human activities affect the physiology or behavior of marine mammals and, if so, whether those effects may lead to changes in survival and reproduction at the population level. We suggest that four elements be included in designing and implementing such a monitoring program. The first is development of a theory of change: a set of mechanistic hypotheses that outline why a given activity might be expected to have one or more measurable effects on individuals and populations, and ideally the magnitude, timing, and duration of the effects. The second element, definition of biologically meaningful effect sizes, ultimately facilitates the development of a monitoring program that can detect those magnitudes of effect with the desired levels of precision. The third element, selection of response variables for monitoring, allows inference to whether observed changes in the status of individuals or populations are attributable to a given activity. Visual observations, passive acoustic and tagging instruments, and direct physical measurements all can provide data that facilitate quantitative hypothesis testing. The fourth element is specification of the temporal sequence of monitoring. These elements also can be used to inform monitoring of the responses of other taxonomic groups to human activities.

Estimating minke whale ( Balaenoptera acutorostrata ) boing sound density using passive acoustic sensors - Stephen W. Martin; Tiago A. Marques; Len Thomas; Ronald P. Morrissey; Susan Jarvis; Nancy DiMarzio; David Moretti; David K. Mellinger (Marine Mammal Science, 2013)
A bstract Density estimation for marine mammal species is performed primarily using visual distance sampling or capture‐recapture. Minke whales in Hawaiian waters are very difficult to sight; however, they produce a distinctive “boing” call, making them ideal candidates for passive acoustic density estimation. We used an array of 14 bottom‐mounted hydrophones, distributed over a 60 × 30 km area off Kauai, Hawaii, to estimate density during 12 d of recordings in early 2006. We converted the number of acoustic cues ( i.e. , boings) detected using signal processing software into a cue density by accounting for the false positive rate and probability of detection. The former was estimated by manual validation, the latter by applying spatially explicit capture‐recapture (SECR) methods to a subset of data where we had determined which hydrophones detected each call. Estimated boing density was 130 boings per hour per 10,000 km 2 (95% CI 104–163). Little is known about the population's acoustic behavior, so conversion from boing to animal density is difficult. As a demonstration of the method, we used a tentative boing rate of 6.04 boings per hour, from a single animal tracked in 2009, to give an estimate of 21.5 boing‐calling minke whales per 10,000 km 2 .

Passive acoustic density estimation of sperm whales in the Tongue of the Ocean, Bahamas - Jessica A. W ard; Len Thomas; Susan Jarvis; Nancy DiMarzio; David Moretti; Tiago A. Marques; Charlotte Dunn; Diane C laridge; Eva Hartvig; Peter Tyack (Marine Mammal Science, 2012)
Long‐term passive acoustic monitoring of marine mammals on navy ranges provides the opportunity to better understand the potential impact of sonar on populations. The navy range in Tongue of the Ocean (TOTO), Bahamas contains extensive hydrophone arrays, potentially allowing estimation of the density of deep diving, vocally active species such as the sperm whale ( Physeter macrocephalus ). Previous visual surveys in TOTO have been of limited spatio–temporal coverage and resulted in only sporadic sightings of sperm whales, whereas passive acoustic observations suggest the species is present year round. However, until now the means of acoustically determining the specific number of individuals in each cluster has been limited. We used recently developed algorithms to identify the number of echolocating whales present during a 42 d study period. We screened a 297 h acoustic data set to determine the proportion of time animals were present; fifty 10 min samples during presence were analyzed to estimate the number of individuals vocalizing during each sample. These counts were combined with an independent estimate of the proportion of 10 min periods when tagged animals vocalize. The estimated average density was 0.16 whales/1,000 km 2 (CV 27%; 95% CI 0.095–0.264). The method is potentially applicable to other areas containing dense hydrophone arrays.

Science on Whales, Submarines, and Conservation Meets the News - David Moretti (Conservation Biology, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Changes in spatial and temporal distribution and vocal behavior of Blainville's beaked whales ( Mesoplodon densirostris) during multiship exercises with mid‐frequency sonar - Elena McCarthy; David Moretti; Len Thomas; Nancy DiMarzio; Ronald Morrissey; Susan Jarvis; Jessica Ward; Annamaria Izzi; Ashley Dilley (Marine Mammal Science, 2011)
The number and distribution of vocalizing groups of Blainville's beaked whales ( Mesoplodon densirostris ) were analyzed before, during, and after multiship mid‐frequency active sonar operations at the US Navy's Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. Groups of foraging animals were isolated by detecting their echolocation clicks using an array of bottom‐mounted hydrophones. Two data sets were evaluated consisting of 115 and 240 h of acoustic data in May 2007 and 2008, respectively. Vocal activity was observed to decline during active sonar exercises and increase upon cessation of sonar transmissions in both data sets. Vocal activity did not recover to preexposure levels in the postexposure time period in 2007 nor in the initial postexposure period in the 2008 data set. Clicks detected during sonar operations were generally found to be on the periphery of the hydrophone field and vocal durations declined for those groups that remained on the range in that time period. Receive levels were calculated for several vocal groups of whales and indicated that animals continued to forage when exposed to sonar at levels as high as 157 dB re: μPa.

An International Quiet Ocean Experiment - Ian Boyd; George Frisk; Ed Urban; Peter Tyack; Jesse Ausubel; Sophie Seeyave; Doug Cato; Brendon Southall; Michael Weise; Rex Andrew; Tomonari Akamatsu; René Dekeling; et al. (Oceanography, 2011)

Development and evaluation of robust molecular markers linked to disease resistance in tomato for distinctness, uniformity and stability testing - Paul Arens; Carmen Mansilla; Daniël Deinum; Laetitia Cavellini; André Moretti; Sophie Rolland; Hanneke van der Schoot; David Calvache; Fernando Ponz; Cécile Collonnier; René Mathis; Diederik Smilde; et al. (Theoretical and Applied Genetics, 2010)

Sighting characteristics and photo-identification of Cuvier’s beaked whales (Ziphius cavirostris) near San Clemente Island, California: a key area for beaked whales and the military? - Erin A. Falcone; Gregory S. Schorr; Annie B. Douglas; John Calambokidis; Elizabeth Henderson; Megan F. McKenna; John Hildebrand; David Moretti (Marine Biology, 2009)